STRATEGI KEPALA SEKOLAH DALAM MEWUJUDKAN MANAJEMEN BUDAYA SEKOLAH YANG EFEKTIF DI SD NEGERI 02 SUKOREJO KABUPATEN PEMALANG - Saparudin, Eko; Dina Hikmah Safariyah; Noor Miyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
School culture management plays a crucial role in creating a conducive learning environment. This study aims to analyze the strategies of school principals in implementing effective school culture management at SD Negeri 02 Sukorejo, Pemalang Regency. Using a qualitative method with a descriptive approach, data was collected through interviews, observations, and document studies. The results indicate that the principal plays a key role in building a positive culture by strengthening shared values, engaging the school community, and implementing programs that support the school's vision and mission. Cultural programs such as